واقع البحث العلمي في جامعة تشرين, ودور الجامعة في الارتقاء بالبحث العلمي "دراسة تقويمية لواقع البحث العلمي من وجهة نظر أعضاء الهيئة التدريسية" - محمد, محمود; حسن, ميسون (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يتناول البحث الحالي واقع البحث العلمي في جامعة تشرين, ودور الجامعة في الارتقاء بالبحث العلمي, وذلك من وجهة نظر عينة من أعضاء الهيئة التدريسية في جامعة تشرين, ولتحقيق أهداف البحث تمّ تصميم استبانة تناولت واقع البحث العلمي ودور الجامعة في تشجيع البحث العلمي وتقديم التسهيلات الداعمة للباحثين وتكوين وتأهيل المهارات البحثية, أضف إلى ذلك الصعوبات التي يعاني منها البحث العلمي, وبعد الدراسة والتحليل توصل البحث إلى النتائج الآتية: 1- يعاني البحث العلمي من عدم مراعاة البحوث العلمية احتياجات سوق العمل, وعدم اهتمام الجهات العامة بالأبحاث العلمية, وعدم تنفيذ مقترحات البحوث العلمية وتوصياتها, وعدم توفير شبكات الحاسب الآلي في مكاتب أعضاء هيئة التدريس, وضعف توفر المراجع والكتب الحديثة, وضعف التسويق للاختراع وتجسيده على أرض الواقع, وضعف الميزانية المخصصة للبحث العلمي في الجامعة. 2- عدم وجود فروق ذات دلالة إحصائية بين آراء أفراد العينة حول واقع البحث العلمي ودوره في الارتقاء بالعمل المؤسساتي تبعاً لمتغير الرتبة الأكاديمية. This paper deals with the current reality of scientific research and the university role in promoting scientific research , from the perspective of a sample of the members of the faculty at Tishreen University, and to achieve the objectives of the research been a questionnaire was made which deals with the reality of scientific research and the role of the university in promoting scientific research and provide facilities in support of the researchers and the training of research skills, in addition to the difficulties experienced by scientific research, and after the study and analysis of research we found the following: 1- scientific research does not take into consideration the needs of the work market, and the public bodies' lack of interest in scientific research, as well as not using the recommendations of scientific research and the failure to provide internet access points in the faculty members' offices, in addition to the poor availability of references and up-to-date books, and poor marketing of the inventions. Indeed, the meagerness of the budget allocated for scientific research at the university. 2- The lack of statistically significant differences between respondents in the reality of scientific research and its role in promoting the work according to the institutional variable academic rank